The Trials of Lady Chatterley, the Modernist Bishop and the Victorian Archbishop: Clashes of Class, Culture and Generations. (4th January 2016) - Mews, Stuart
Abstract : 'Now firmly established as a modernist novelist', D. H. Lawrence (1885–1930) remains a controversial writer, especially for the ambiguity of his attitudes to fascism and feminism. This essay considers the role played by the then forty-one-year-old bishop of Woolwich, John Robinson, in offering evidence for the defence in the Old Bailey trial in 1960 which acquitted Penguin Books of obscenity in publishing Lawrence's novel Lady Chatterley's Lover . In taking part in the trial Robinson acquired notoriety (or credit). His public admiration for Lawrence's writing placed him at odds with the two postwar archbishops, Geoffrey Fisher (Canterbury) and Cyril Garbett (York). In the words of Mark Roodhouse in a pioneering article, 'for ecclesiastical historians the Lady Chatterley trial not only reveals changing social attitudes but also growing division within the Church of England between "two Christianities" over the way to respond to these changes'. Robinson did not receive further advancement in the Church.